Attitudes Toward Genetics and Genetic Testing Among Participants in the Jackson and Framingham Heart Studies. (July 2019) - Saylor, Katherine W.; Ekunwe, Lynette; Antoine-LaVigne, Donna; Sellers, Deborah E.; McGraw, Sarah; Levy, Daniel; Splansky, Greta Lee; Joffe, Steven
Genetic analysis has become integral to many large cohort studies. However, little is known about longitudinal cohort study participants' attitudes toward genetics and genetic testing. We analyzed data from a survey of participants in the Jackson Heart Study ( n = 960), Framingham Heart Study ( n = 955), and Framingham Heart Study–Omni Cohort ( n = 160). Based on a three-question attitude scale, most participants had positive attitudes toward genetic testing (median score = 4.3-5/5). Participants were also asked to select words to describe their attitudes toward genetics. More respondents endorsed the positive words "hopeful" (60%-70%), "optimistic" (44%-64%), "enthusiastic" (35%-43%), or "excited" (28%-30%) than the negative words "cautious" (35%-38%), "concerned" (25%-55%), "worried" (6%-13%), "pessimistic" (2%-5%), or "horrified" (1%-5%). Characteristics associated with favorable attitudes were greater genetics knowledge, higher subjective numeracy, experience with genetic testing, less frequent religious attendance, and not being employed. These findings demonstrate variation in attitudes even among participants in long-standing cohort studies, indicating a need for ongoing participant engagement and education.